Genetics and the relationship between the virus and the host organism infected with SARS-COV-2 - Schröder , Verginica; Mitea , Gabriela; Iancu, Irina Mihaela; Iancu, Valeriu; Honcea, Adina; Stoicescu, Ramona Mihaela (Technium BioChemMed, 2023)
Human genetic diversity is shaped by both demographic and biological factors and has fundamental implications for understanding the genetic basis of disease. Understanding how some genes influence the manifestation of SARS-CoV-2 viral infection, is a desideratum of modern approaches to personalized therapy. With genome-wide prediction of individual pharmacological response this information can be used to obtain new pharmacological targets, and with them new active substances. All this information reinforces the concept of customized medicine, a concept that was utopian for a while, but with technological advances in molecular analysis, this concept is starting to become a reality. This study is a short review highlighting the main components of the genetic variations in the relationship between the virus and the host organism. Individual variations of genes and their proteins expressions are also a key component in the process of understanding induced immunity after disease as well as after vaccination. Genetics of human cell membranar systems used for virus integrations host and genetics of human intracellular signalling are short presented.